(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Women today have greater influence than they did in the past. In an effort become financially independent, women are now using the skills and initiative necessary to anticipate needs and bring new ideas to market in the form of an entrepreneur. By delving into the experience of a few female entrepreneurs in the Kakching area of Kakching District of Manipur, the study seeks to understand what motivates women to start their own business by taking financial risk, the nature of barriers to the sector in which women entrepreneurs operate, the difficulty in accessing capital for expansion, gender-based discrimination toward women’s entrepreneurship and the need to maintain a balance between work and family life. The main purpose of this study is to determine the basic motivations that encourage women to become entrepreneurs and how they overcome the obstacles they encounter on the way to doing business. Furthermore, it aims to find out what is more beneficial for them to sustain their business for future growth. A case study in the entrepreneurship journey of Padma Shri Moirangthem Muktamani for her outstanding skills in shoe knitting is the core of the paper.